Downregulation of circLIFR exerts cancer-promoting effects on hepatocellular carcinoma in vitro - Ji, Jingzhang; Tang, Jialyu; Ren, Ping; Cai, Wenpin; Shen, Meina; Wang, Qiunan; Yang, Xiaoyun; Chen, Wei (Frontiers in Genetics, 2022)
Hepatocellular carcinoma (HCC) is one of the most fatal malignant tumors worldwide. Circular RNAs (circRNAs) are a special type of RNA that lacks the 5′ and 3’ ends. The functional roles of circRNAs in HCC remain largely unknown. Using high-throughput sequencing, we found several differentially expressed circRNAs in HCC tissues compared with nearby normal tissues. Among them, circRNA derived from the LIFR gene, named circLIFR, was significantly downregulated in HCC. Intriguingly, circLIFR overexpression in SK-Hep-1 cells promoted cell growth and invasion. RNA pull-down and mass spectrometry detection revealed circLIFR interacting with TANK binding kinase 1 (TBK1). Anti-TBK1 RIP confirmed the interaction between circLIFR and TBK1. TBK1 is a serine/threonine kinase that regulates several signaling pathways, including the NF-κB pathway. TBK1 inhibitors inhibit NF-κB activation. Overexpression of circLIFR overcame the in-hibitory function of TBK1, resulting in the upregulation of several genes, including MMP13, MMP3, VEGF, and MAPK. This study shows that the downregulation of circLIFR in HCC has a can-cer-promoting effect by interacting with TBK1 to promote the activation of downstream NF-κB pathway genes related to cell proliferation, migration, and invasion. This novel finding reveals the diversity of circRNA functions in HCC and provides novel insights into the role of circRNAs.